TAX REVENUES FOR LOCAL GOVERNMENTS IN TÜRKİYE - AY, Şahin (SSD Journal, 2025)
The serious increase in urban populations with the industrial revolution continued for many years and caused the settlements to have their own needs. In the discussions about who will solve these problems, sometimes the central government should solve them, sometimes it is the duty of local governments, and sometimes both should be solved together. In this study, it was seen that the revenues of local governments were insufficient in Türkiye. It is known that the share of tax revenues among local government revenues between 2006 and 2024 was around 10%. The fact that the rate of tax revenues among central government revenues is very high has revealed the fact that such a situation should also be the case for local governments. However, when different practices in the world are examined, it is seen that the governance styles of countries where tax revenue shares in local governments are high are different from Türkiye. Since it is known that control is in the central government within the unitary state structure, it would be more efficient to increase the shares to be transferred from the central government instead of practices such as imposing new taxes, increasing existing tax rates that will burden taxpayers, or transferring the collection of existing taxes that will create tax collection costs to local governments.